A critique of the Uganda district league table using a normative health system performance assessment framework - Christine KirungaTashobya; Freddie Ssengooba; Juliet Nabyonga-Orem; Juliet Bataringaya; Jean Macq; Bruno Marchal; Timothy Musila; Bart Criel (BMC, 2018)
Abstract Background In 2003 the Uganda Ministry of Health (MoH) introduced the District League Table (DLT) to track district performance. This review of the DLT is intended to add to the evidence base on Health Systems Performance Assessment (HSPA) globally, with emphasis on Low and Middle Income Countries (LMICs), and provide recommendations for adjustments to the current Ugandan reality. Methods A normative HSPA framework was used to inform the development of a Key Informant Interview (KII) tool. Thirty Key Informants were interviewed, purposively selected from the Ugandan health system on the basis of having developed or used the DLT. KII data and information from published and grey literature on the Uganda health system was analyzed using deductive analysis. Results Stakeholder involvement in the development of the DLT was limited, including MoH officials and development partners, and a few district technical managers. Uganda policy documents articulate a conceptually broad health system whereas the DLT focuses on a healthcare system. The complexity and dynamism of the Uganda health system was insufficiently acknowledged by the HSPA framework. Though DLT objectives and indicators were articulated, there was no conceptual reference model and lack of clarity on the constitutive dimensions. The DLT mechanisms for change were not explicit. The DLT compared markedly different districts and did not identify factors behind observed performance. Uganda lacks a designated institutional unit for the analysis and presentation of HSPA data, and there are challenges in data quality and range. Conclusions The critique of the DLT using a normative model supported the development of recommendation for Uganda district HSPA and provides lessons for other LMICs. A similar approach can be used by researchers and policy makers elsewhere for the review and development of other frameworks. Adjustments in Uganda district HSPA should consider: wider stakeholder involvement with more district managers including political, administrative and technical; better anchoring within the national health system framework; integration of the notion of complexity in the design of the framework; and emphasis on facilitating district decision-making and learning. There is need to improve data quality and range and additional approaches for data analysis and presentation.